Ad Hoc Grid Resource Management: Grid Security - Kavecky, Slavomir; Martincova, Penka (Communications - Scientific letters of the University of Zilina, 2016)
The purpose of security in ad hoc grid environments is to support secure execution of tasks on shared resources and to protect the resources from malicious user actions. The concept of trust management is capable to solve the security issues by incorporating trust into the process of decision making. The quality of the decisions is dependent on a correct assessment and representation of trustworthiness assigned to the potentially collaborating parties. In most cases the value of trustworthiness is derived at least from direct trust and recommendations, but other factors as risk, uncertainty, context dependent information and attributes characterizing the task and the shared resource should be included in the derived value as well. This paper presents a specification of parameters relevant for an accurate trust evaluation.